Analysis of Swear Language in the Coastal Community of Kampung Bulang Bawah Tanjungpinang: Analisis Bahasa Makian pada Masyarakat Pesisir Kampung Bulang Bawah Tanjungpinang - Rizki Handika; Ahada Wahyusari; Legi Elfitra (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The data collection method was carried out using a descriptive method. Descriptive research is a scientific study carried out to obtain information about the status of symptoms at the time the research was carried out so that it can be described systematically, without treating the observed variables. Next, the steps taken in cursing in the Coastal Community of Kampung Bulang Bawah, Tanjungpinang City, namely: the data was transcribed into Indonesian to get an idea of ​​the harsh expressions of the Coastal Community of Kampung Bulang, read the data carefully and repeatedly. -data that has been obtained, data selected and classified according to the research problem, generalization or making conclusions from the data obtained, and compiling a report on the results of the analysis in a report. The results of this research show that the forms of swearing used by the Coastal Community of Kampung Bulang Bawah Tanjungpinang City are divided into rude expressions in the form of words such as melonte, puki, bitch, smut, and mentel. The greetings are in the form of phrases, such as puki die, slave bitch, and kelentet die. Based on the swear words used by the Coastal Community of Kampung Bulang Bawah, Tanjungpinang City, they are in situations or states of anger or annoyance, and joking, as well as familiarity.